Testing macroevolutionary skull patterns using tetrapod cranial networks - Matos, Paula Catarina Silva de (2019)
The vertebrates’ skull houses the brain and important sensory organs. This anatomic structure has suffered various changes and specializations that recapitulate the evolutionary process. This variability, its complexity and easy preservation makes it one of the standard characteristics used in comparative anatomy and evolutive biology for instance in the classification of vertebrates and phylogenetic reconstruction. A total of 25 species were considered: Acanthostega gunnari; 14 species within Mammalia including the groups Sirenia, Hyracoidea, Carnivora, Cetartiodactyla and Primates and 10 Reptilia from Crocodylia, Neotheropoda, Rhynchocephalia, Squamata and Testudines. All the collected data was analyzed through three different softwares: PAUP, for phylogenetic analysis, Gephi to build networks of contacts from the skull and Rstudio for statistics. In this study we show how phylogeny of an animal can be inferred to Class level using exclusively information regarding skull bone contacts but there is not enough information contained on the skull alone to recreate phylogenetic paths to build complete phylogeny.